Low Energy Adaptive Clustering Hierarchy Routing Protocol for Wireless Sensor Network - Veronica Windha Mahyastuty; A. Adya Pramudita (Universitas Ahmad Dahlan, 2014)
Wireless Sensor Network (WSN) is a network composed of many sensor nodes distributed in a region, and is used to monitor and gather information about certain phenomena in the physical environment. A sensor node typically has limited power, which must be taken into consideration in designing the routing protocol of a WSN. One of the routing protocols that can increase the energy efficiency of WSN is Low Energy Adaptive Clustering Hierarchy (LEACH). In this research, the performance of LEACH, namely energy consumption and lifetime is evaluated using NS-2. Simulation results show that the number of nodes and clusters affect the optimum number of clusters and the device lifetime, which in turn will affect the energy consumption level as well as the energy efficiency.